Optimalisasi Pengelolaan Keuangan Daerah Melalui Cost Control Inklusif Untuk Mengurangi Disparitas Ekonomi - Elga Naya Maharani (Journal of State Economic Research, 2025)
This research proposes an Inclusive Cost Control (CCI) framework to address fiscal decentralization failures in reducing Indonesia's regional economic disparities. Although authority delegation aims to enhance efficiency, budget allocation ineffectiveness and low productive spending remain structural challenges. Utilizing a Systematic Literature Review and Barro’s growth model analysis, this study integrates Cost Accounting systems with Performance-Based Budgeting within the Public Financial Management framework. Findings indicate that the CCI strategy enables local governments to rationalize non-critical operational costs to protect physical and human capital investments. CCI implementation is projected to increase public service effectiveness by 25% and infrastructure quality by 30%. By optimizing Value for Money, CCI serves as a strategic policy instrument to ensure pro-equity productive spending allocations. In conclusion, transitioning from short-term cost-cutting to structural cost control is vital to minimize the trade-off between fiscal efficiency and regional equity for the achievement of inclusive, fair, and sustainable regional economic development.